Real-time imaging of cortical and subcortical control of muscle sympathetic nerve activity in awake human subjects - James, Cheree; Macefield, Vaughan G.; Henderson, Luke A. (NeuroImage (Orlando, Fla.), 2013)
Blood pressure is controlled on a beat-to-beat basis through fluctuations in heart rate and the degree of sympathetically-mediated vasoconstriction in skeletal muscles. By recording muscle sympathetic nerve activity (MSNA) at the same time as performing functional magnetic resonance imaging (fMRI) of the brain, we aimed to identify cortical structures involved in central cardiovascular control in awake human subjects. Spontaneous bursts of MSNA were recorded via a tungsten microelectrode inserted percutaneously into the peroneal nerve of 14 healthy subjects in a 3T MRI scanner. Blood Oxygen Level Dependent (BOLD) contrast – gradient echo, echo-planar – images were continuously collected in a 4s ON, 4s OFF sampling protocol. MSNA burst amplitudes were measured during the OFF periods and BOLD signal intensity was measured during the subsequent 4s period to allow for neurovascular coupling and nerve conduction delays. Group analysis demonstrated regions showing fluctuations in BOLD signal intensity that covaried with the intensity of the concurrently recorded bursts of MSNA. Signal intensity and MSNA were positively correlated in the left mid-insula, bilateral dorsolateral prefrontal cortex, bilateral posterior cingulate cortex and bilateral precuneus. In addition, MSNA covaried with signal intensity in the left dorsomedial hypothalamus and bilateral ventromedial hypothalamus (VMH). Construction of a functional connectivity map revealed coupling between activity in VMH and the insula, dorsolateral prefrontal cortex, precuneus, and in the region of the left and right rostroventrolateral medulla (RVLM). This suggests that activity within suprabulbar regions may regulate resting MSNA by projections to the premotor sympathetic neurons in the rostroventrolateral medulla. ► Very little is known about the control of sympathetic drive in awake humans. ► We recorded brain activity and sympathetic activity concurrently in awake humans. ► Cortical and hypothalamic regions fluctuated with spontaneous sympathetic activity.► Ventromedial hypothalamus activity covaried with rostral ventrolateral medulla. ► Suprabulbar regions regulate resting sympathetic activity via medulla.